The Role of Emotion Regulation in Reducing Emotional Distortions of Duration Perception - Tian, Yu; Liu, Peiduo; Huang, Xiting (Frontiers in Psychology, 2018)
Emotional events, especially negative ones, are consistently reported to last longer than neutral events. Previous studies suggested that this distortion of duration perception is linked to arousal and attention bias in response to emotional events. Reappraisal and suppression, arguably the most effective strategies for emotion regulation, have been demonstrated to decrease such arousal and attention bias. The present study investigated whether reappraisal and suppression can reduce emotional distortions of duration perception. Seventy-eight Chinese undergraduates were recruited as paid participants and randomly assigned to nonregulation, reappraisal, and suppression groups. Before they performed a temporal bisection task involving presentation of emotional pictures for different durations, the groups were each given one of three different sets of instructions requiring them to passively perceive, reappraise, or suppress the emotions of the pictures. The results indicated that the distortion of duration perception occurred only in the nonregulation group, suggesting that it can be effectively reduced by reappraisal and suppression.